Evaluasi Pelayanan Sarana Dan Prasarana Proteksi Kebakaran Pada Permukiman Perkotaan - Pipin Yunita Sari; Soekmana Soma; Linda Dwi Rohmadiani (TATALOKA, 2021)
The incidence of fires in the city of Sidoarjo in the last 5 years has increased. The main causes of the majority of fires were settlement activities and weeds. The aim of this study was to evaluate the level of fire protection facilities and infrastructure services in the urban settlements of Sidoarjo City based on Minister of Public Works Regulation No.20 / PRT / M / 2009 concerning Technical Guidelines for Fire Protection Management. The study area consisted of Sidoarjo District, Candi District and Buduran District. The research approach used is descriptive evaluative research. The results showed that the level of fire protection facilities and infrastructure services in the city of Sidoarjo was still 48%, it needed an increase in the aspects of the completeness of the Fire Extinguishers building, the availability of fire stations and hydrants as well as increasing community participation.